Murid rodents (Muriformes, Muridae) from Trascarpathia in the collections of Kyiv zoological museums - Barkasi, Z. (Збірник праць Зоологічного музею, 2014)
In scientific collections of the National Museum of Natural History, NAS of Ukraine and the Zoological Museum of Kyiv Taras Shevchenko National University are preserved 482 samples, six species of Muridae rodents collected from 1940 to 1990. Specimens were collected in all altitudinal zones of the region. The article containes general characteristics of the collections and brief description of genera and species of murids according to the latest fauna surveys of the region. В научных фондах Национального научно-природоведческого музея НАН Украины и Зоологического музея Киевского национального университета имени Тараса Шевченко хранятся 482 образца 6 видов грызунов семейства Muridae, собранных с 1940 по 1990 год. Сборами охвачены все географические зоны региона. В статье представлена общая характеристика исследованных коллекций, обзор родов и видов мышиных в свете последних списков родентофауны региона. У наукових фондах Національного науково-природничого музею НАН України та Зоологічного музею Київського національного університету імені Тараса Шевченка зберігаються 482 зразки 6 видів гризунів родини Muridae, зібрані з 1940 до 1990 року. Зборами охоплено всі географічні зони регіону. В статті подано загальну характеристику досліджених колекцій, огляд родів і видів мишевих у світлі останніх списків родентофауни регіону.